Nærværsformer: Mod en konstruktivistisk omgang med performativitet - Lehmann, Niels (Peripeti, 2021)
Using Erika Fischer-Lichte’s attempt to pin down the ontology of performative art, the article defends a constructivist approach to performativity. The first half of the article consists of an argument for placing Fischer-Lichte’s theory within the poetological framework of the avantgarde. With the help of the notion of operative closure lifted out of systems theory as presented by Niklas Luhmann, the second half presents the constructivist approach which is seen as opposed to performance ontology as such and, in particular, the avangarde version of this approach.